Koleje pod specjalnym nadzorem : Służba Bezpieczeństwa jako instrument nadzoru państwowego nad koleją w latach 1957–1980, cz. 1 (1957–1975) - Bereszyński, Zbigniew (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2020)
Due to their strategic importance, the railways were subject to particular surveillance by the state security apparatus of the Polish People’s Republic. Since 1957, the related tasks were carried out by department III of the Security Service (Służba Bezpieczeństwa), which centered its operations on broadly understood economy issues.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne